Inflammatory Bowel Disease and Pregnancy: Evidence, Uncertainty and Patient Decision-Making - Flavio M Habal; Varun Kapila (Canadian Journal of Gastroenterology)
Inflammatory bowel disease (IBD) often affects women during their child-bearing years. Management of a pregnant IBD patient, or a patient contemplating pregnancy, poses unique challenges and can be quite daunting. Knowledge of the basic interplay among disease, normal host physiology and pregnancy is vital to managing these patients. One of the most important advances in the management of IBD over the past decade has been the finding that normal pregnancy outcomes can be achieved when a woman enters the pregnancy in remission. New insights into the safety of a wider spectrum of drugs in these patients has allowed for increased success in IBD management. The evidence supporting medical interventions including biological therapy such as antibodies to tumour necrosis factor agents is reviewed. Once the treating physician understands this complex relationship, management of the pregnant IBD patient can often become a rewarding experience.